2010
DOI: 10.1111/j.1423-0410.2010.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing cord blood from premature infants into autologous red‐blood‐cell products for transfusion

Abstract: UCB can be processed into autologous products for premature infants. Shelf-life is limited to 14-21 days and compares unfavourably to stored whole blood. Considering the early transfusion needs in these infants, a short shelf-life would not be a practical objection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…Cord blood units without clots or signs of hemolysis, when fractionated, have red cells with acceptable biochemical and functional properties during storage [13,16]. Accordingly, hematocrit gain after transfusion and time intervals between transfusions were similar in UCB-RBCs and A-RBCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cord blood units without clots or signs of hemolysis, when fractionated, have red cells with acceptable biochemical and functional properties during storage [13,16]. Accordingly, hematocrit gain after transfusion and time intervals between transfusions were similar in UCB-RBCs and A-RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, umbilical cord blood (UCB) collection and processing to obtain RBC products for autologous transfusion have been extensively investigated [7,8,9,10,11,12]. The refinement of techniques of collection, processing and storage of UCB allowed the production of UCB-RBC units suitable for clinical use [13,14]. However, the small volume of UCB collected does not allow an adequate coverage of transfusion needs of preterm infants and this practice has nowadays been abandoned [12].…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that autologous RBCs could be harvested from CB collected after premature birth and, if successful, could cover up to 58% of the transfusion needs . These premature CB‐derived RBC transfusion products had a shorter shelf life (maximally 21 days) compared to adult RBCs, which can be stored for 35 days . To obtain RBCs, the premature CB was buffy coat depleted by centrifugation and the removed buffy coats contained approximately 40% of the white blood cells (WBCs).…”
mentioning
confidence: 99%
“…We aimed to set up a simple one‐step culture protocol using only human proteins and recombinant human cytokines in the culture medium. In view of the practical transfusion needs of premature infants, we focused on the cultured cells that could be obtained within 21 days of expansion, which could theoretically supplement autologous CB RBCs, which have a shelf life up to 21 days . To test the efficiency and efficacy of this culture protocol, we compared both premature and full‐term CB and cells derived from adult blood and bone marrow (BM).…”
mentioning
confidence: 99%
“…In contrast, cord RBCs deteriorate much faster under the same conditions and cannot be stored for more than 14 days without significant decrease in quality [28, 37]. Cryopreservation and subsequent storage at ultra-low temperatures may preserve cord RBCs and maintain a high quality of cord RBCs for use in intrauterine and neonatal transfusions.…”
Section: Introductionmentioning
confidence: 99%